Baseline predictors of cognitive change in the treatment of major depressive episode: systematic review - Zoe A. Barczyk; Katie M. Douglas; Richard J. Porter (BJPsych Open, 2020)
Background Cognitive impairment is a core feature of depression and has a negative effect on a person's functioning, in psychosocial and interpersonal areas, and on workforce performance. Cognitive impairment often persists, even with the remittance of mood symptoms. One potential way of improving treatment of cognitive impairment would be to identify variables that predict cognitive change in patients with depression.